The Heritage Buddhist Manuscripts of Ladakh Tibetan Buddhist Canons and the Perfection of Wisdom Sutra (HIMALAYA, 2020)
The history of the earliest transmission of Indian Buddhism to Tibet in the 7th– 8thcenturies is in essence the story of the transmission of its scriptures. Tibetan translations of Sanskrit texts from the early imperial period, along with manuscripts translated from the 11thcentury onwards, contributed to the formation of Buddhist scriptural collections. Today different versions of the Tibetan Kangyur survive in the interior and at the margins of the Tibetan cultural world. This Perspectives piece serves as a modest introduction to the illustrated Prajñāpāramitā manuscripts and handwritten Buddhist canons preserved in the Indian north-western Himalayas. Their further study will undoubtedly advance our knowledge of Ladakh’s cultural and religious heritage and offer critical insights in the formation of Tibetan canonical literature. The purpose of this overview is to highlight the results of initial findings, explain how they relate to existing knowledge, and raise important themes for additional enquiries.